THE EFFECT OF PROBIOTIC TREATMENT ON OBESITY-RELATED CHANGES IN THE PERIODONTIUM OF OBESE RATS - M. Skrypnyk; K. Neporada; M. Spivak (Biotechnologia Acta, 2025)
Obesity is a significant global health concern associated with various systemic diseases, including periodontitis. Probiotics have shown promising outcomes as an adjunctive therapy in both clinical and microbiological parameters; however, their impact on obesity-induced periodontal alterations remains unclear.